Land use land cover changes and extreme precipitation events along Carajás Railroad in the eastern Brazilian Amazon - Alves, Maísa Quintiliano; Justino, Flávio; de Oliveira, Rubens Alves; de Alencar, Carlos Augusto Brasileiro; Alvino, Francisco Cássio Gomes; Coelho, Renan Rodrigues (Theoretical and applied climatology, 2024)
The importance and vulnerability of municipalities in the eastern Amazon led to the evaluation of the distribution of seasonal precipitation and extreme events over protected and deforested sites along the Carajás Railroad (EFC) based on three datasets: Brazilian Daily Weather Gridded Data (BR-DWGD), European Reanalysis (ERA5-Land), and Climate Hazards Group InfraRed Precipitation with Station (CHIRPS). The main purpose is the understanding of the relationship between local land use change and the occurrence of extreme climate events. Results suggested that large-scale deforestation has a regional impact occasionally outweighing local effect. Significant trends reveal a general pattern of drought that has been more intense in the north of the study area, regardless of land cover, whether preserved or deforested. Moreover, the dry season is getting drier, but the wet season is not getting wetter over the entire area, as Carajás National Forest and Curionópolis (southern sector) deliver positive and accentuated trends in the rainy season. Extreme events are becoming more frequent. The number of consecutive dry days has increased in the north revealing an extension of dry periods, whereas, the maximum one-day precipitation has soared in the south indicating the intensification of rainfall. CHIRPS provides stronger correlations with the standard dataset (BR-DWGD), as both furnish primary data based on rain gauges observations. It also outperforms ERA5-Land in annual and seasonal analyses, which does not invalidate the latter as a great alternative to use in data-poor locations. Ultimately, further research and technology implementation were recommended to improve reforestation efforts given the reported results.